Offshore Wind Roadmap for Vietnam - World Bank (World Bank, Washington, DC, 2021)
This roadmap provides strategic analysis of the offshore wind development potential in Vietnam, considering the opportunities and challenges under different growth scenarios. It is intended to provide evidence to support the Government of Vietnam in establishing policy, regulations, processes, and infrastructure to enable successful growth of this new industry. It was initiated by the World Bank country team in Vietnam under the umbrella of the World Bank Group’s Offshore Wind Development Program, which aims to accelerate offshore wind development in emerging markets, and was funded by the Energy Sector Management Assistance Program (ESMAP).